Early transplantation into a vesicostomy: a safe approach for managing patients with severe obstructive lesions who are not candidates for bladder augmentation. Issue 4 (August 2018) - Viswanathan, A.; Leffler, T.; Paloian, N.; Cain, M.; McKenna, P.H.
Summary: Introduction: Management of severe antenatally detected oligohydramnios with and without obstruction is improving with the result that more fetuses are surviving with early renal failure. Significant advances have occurred in all specialties involved in the management of these patients. All these specialties working together have resulted in the survival of more patients born with renal failure. Objective: The aim of this study is to highlight the medical advances in antenatal management of fetal oligohydramnios and pulmonary hypoplasia and to demonstrate that transplantation into a diverted urinary system is safe and leads to good outcomes. Study design: A case series of five patients were presented who, at the study center's respective facilities, recently underwent renal transplantation into bladders drained by cutaneous vesicostomy after extensive bladder evaluation and whose clinical cases highlight the aim of this study. Results: A total of 5 patients were reviewed. Renal failure was caused by posterior urethral valves in four patients, and in one patient Eagle-Barrett syndrome. One patient received an amnio-infusion and attempted antenatal bladder shunt. One patient was ventilator dependent until 24 months, and required a tracheostomy, while two patients were ventilator dependent for the first few months of life. Three of five patients were dialysis dependent. Patient age at transplantation ranged from 20 to 61 months. All patients were poorly compliant pre-transplant and had bladder capacities ranging from 10 mL to 72 mL. Months since follow-up ranged from 3 to 64 months. Creatinine levels prior to transplant ranged from 1.9 to 5.6. During the follow up period, this range decreased to 0.13 to 0.53. Two of five patients had UTI episodes since transplantation. Patient A showed Banff Type 1A acute T-cell mediated rejected approximately two months after transplant, but subsequent biopsies have been negative for rejection. Patient A also required a vesicostomy revision approximately two months after transplant and balloon dilation of UVJ anastomosis three months after transplant. Discussion: Vesicostomy is an especially attractive option to manage children with small bladders to accommodate the high urinary output that occurs after transplantation in infants who require an adult kidney. Recent advances in antenatal management such as amnioinfusion for oligohydramnios have made significant impacts in pulmonary and renal management of this patient population over recent years. Conclusion: This report provides further support for the use of vesicostomy as an option for surgical management of patients with renal failure with oligohydramnios and severe obstructive lesions identified antenatally. It also indicates the need to update the criteria for antenatal management of oligohydramnios in obstructive and anephric patients. Criteria A B C D E Cause of renal failure Posterior urethral valves Eagle-Barrett syndrome Posterior urethral valves Posterior urethral valves Posterior urethral valves Antenatal interventions Amnioinfusions; attempted bladder shunt None None None None Pulmonary hypoplasia/ventilator dependency Yes, ventilator dependence until 24 months, requiring tracheostomy Ventilator dependence for the first few months of life None Yes, ventilator dependence for first few months of life None Dialysis dependency Yes, was on peritoneal dialysis until transplantation No No Yes, peritoneal dialysis Yes, peritoneal dialysis Age at transplantation to diverted vesicostomy 20 months 24 months 26 months 46 months 61 months Pretransplant bladder capacity and compliance 30 ml; poorly compliant 45 ml; poorly compliant 10 ml; poorly compliant 72 ml; poorly compliant 26 ml; poor compliance Follow-up in months since transplantation 12 months 12 months 3 months 16 months 64 months Creatinine before transplantation 3.6–5.6 2.2–3.3 1.9–2.8 4.08 3.2–3.7 Creatinine range during follow-up period 0.17–0.36 0.13–0.38 0.17–0.34 0.35 0.30–0.53 Episodes of UTI since transplantation Yes, multiple None Yes, E. coli pyelonephritis ∼2 months after transplantation None None Evidence of transplant rejection Banff Type 1A acute T-cell–mediated rejection noted ∼2 months after transplantation; but the patient has had multiple subsequent biopsies negative for rejection None to date None to date None None Surgical revision of vesicostomy or any subsequent procedures Yes, revision of vesicostomy 2 months after transplantation & balloon dilation of UVJ anastomosis 3 months after transplantation None None after the transplantation/vesicostomy, but the patient had bilateral end cutaneous ureterostomies performed at 6 days of age None None